Фізична активність та спортивні звички студентів ЗУІ - Чегіль Аніко; Csehil Anikó; Aniko Chehil (Видавництво «Код», 2024)
Резюме. Спорт, подібно до інших звичок здорового способу життя, має зароджене коріння у ранньому дитинстві, тому важливо, щоб у цей період сформувалася любов до фізичних вправ, а діти звикли до регулярної фізичної активності. Підлітки та молодь становлять ту категорію людей, для якої первинна профілактика обіцяє найбільший довгостроковий успіх, а зміна шкідливих звичок найбільш можлива саме в цей час. Приблизно половина старшокласників і лише третина студентів закладів вищої освіти займаються спортом регулярно. Рівень активності зменшується у дорослому віці. Це свідчить про очевидні відмінності у звичках по відношенню до спорту, враховуючи соціальні фактори. Тому важливо, щоб університетські роки становили можливість для занять спортом у рамках організованої діяльності, консультування з питань здорового способу життя, впровадження та свідомого усвідомлення профілактичної ролі спорту.

Abstract. Sport, like other health behaviours, is linked to early childhood patterns, so it is important to develop a love of exercise and get children used to regular physical activity. Adolescents and young people are the population for whom primary prevention has the greatest potential for long-term success and when it is most likely to change harmful behaviours. Aproximately half of the secondary school students and only one third of those in higher education play sport regularly. Activity levels fall even further in adulthood. This suggests that there are clear differences in sporting habits across social background factors. It is therefore important that the university years provide the last opportunity to practise sport in an organised setting, to provide lifestyle advice and to promote and raise awareness of the preventive function of sport. Lack of time, bad experiences and lack of interest were noted as the most influential factors influencing the lack of sports activities. In these cases, the majority chose these arguments. Overall, the satisfaction results suggest that lack of personal motivation is the most prominent problem. Regarding the choice of sport, there are differences both in terms of gender and in the types of athletes, where there is a strong relationship between the types of athletes and the choice of sport (p=0.009). In the case of women, both types of athletes value cycling more highly, and swimming is a popular sport to about equal extent. However, there is a difference in the choice of sport among athletes – volleyball and fitness among athletes, and aerobics among non-athletes are more popular. Among male students, the priorities in choosing a sport differ significantly depending on the type of athlete: football remains popular among athletes, which is connected with the growing importance of fitness, and basketball is also significant. Among those who do not do sports, the most popular are swimming and horse riding (18% each). Recently, the essence of sports needs of students of higher educational institutions has changed. This is caused, on the one hand, by the motivation of students, and on the other – by changes in opportunities. When planning sports services and leisure programs, it is necessary to take into account the new needs of the younger generation, the changed worldview and changes in the requirements for the place and conditions of sports.
Physical activity and sports habits of college students
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014094
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-7
Keywords: студентська молодь; фізична активность; спорт; заклади вищої освіти